Adaptation and validation of the social skills scale for intercultural primary school pupils - Aranda-Vega, Eva María; Ortiz-Marcos, José Manuel; Tomé-Fernández, María (Frontiers in Education, 2023)
Social skills are understood as a crucial element in diverse educational contexts. Therefore, and following a review of the scientific literature, the aim of this research was to adapt and validate a scale that diagnoses social skills in young people aged 6 to 12 years, and who are in culturally diverse contexts. The study included expert judgement, exploratory factor analysis EFA (n=761) and confirmatory factor analysis CFA (n=803), using a sample of 1564 primary school students from different localities in Andalusia that constitute border cities in southern Spain, which have a great cultural, ethnic and religious diversity reflected in their classrooms. The resulting scale consists of 33 items and five dimensions, with psychometric properties that give it validity and reliability. This resource offers a valuable tool for the diagnosis of social skills in primary school pupils, particularly in schools with a high cultural and religious diversity.